Dario Martinelli, "Give Peace a Chant: Popular Music, Politics, and Social Protest", Springer International, Cham, 2017. - Blake, David K. (Analitica. Rivista online di studi musicali, 2017)
Dario Martinelli’s Give Peace a Chant: Popular Music, Politics, and Social Protest is a critical analysis of the ways that popular music can express social politics. The topic of the politics of popular music is not new since social politics have long motivated the study of popular culture. What is distinct in Martinelli’s book, and curious, is that it attempts to study how popular music takes on political meaning without itself being explicitly political. Instead, Give Peace a Chant intends to provide layers of semiotic taxonomies for more precise analysis of popular music’s political aims. The book’s purpose immediately called to mind one of the most formative essays in popular music historiography, Stuart Hall’s 1981 Notes on Deconstructing the Popular. Hall’s essay, written at the onset of the serious scholarly analysis of popular culture, argued that the academic study of popular culture should not be concerned with taxonomizing the genres, styles, and forms that constitute the cultural sphere at a given time. Instead, scholars should attend to the historical irruptions produced by power relations, new social forces, and technological developments that transform not only common-sense understandings of what popular culture is, but also the political potentials of the cultural field.